PERBANDINGAN IMBAL HASIL KONTRAK MUDHARABAH DAN PARTISIPASI MODAL DALAM PENGHIMPUNAN DANA BANK SYARIAH DI INDONESIA - Amaroh, Siti (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
This study aims to compare the return between mudharabah deposits and equityparticipating in Indonesia Islamic banking and also to examine the factors that affect the returns. Employee monthly data of 3 Islamic banks over the period 2006-2011 and examined by regression panel model. This research results several substantial findings. First, return on mudharabah deposits is lower than return on equity participating. Second, return on mudrabah deposits is significantly affected by return on assets, profit attributable to third party deposits as percentage of operating profit, and total deposit to total assets. Third, return on equity is also significantly affected by return on assets, profit attributable to equity holders as a percentage of operating profit, and total equity to total assets. Fourth, return on assets affects more higher return on equity than the return on mudharabah deposits.